RANCANG BANGUN WEB PROFIL PUSAT PENELITIAN DAN PENGABDIAN POLITEKNIK NEGERI AMBON - Victor Febian Puturuhu; Ari Permana L, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
PPPM (Center for Research and Community Service) of Ambon State Polytechnic which functions to implement and evaluate activities in the field of Research and Community Service. The Center for Research and Community Service has the task of coordinating, documenting the implementation of research and community service activities and participating in efforts to control the administration of the necessary resources. The current condition that occurs is that there is no media that can be used by the P3M Polnam Party to publish information related to research activities carried out, including research and community service activities that use PNPB Polnam funds, Usually announced on the notice board or from the P3M Polnam staff, the problem that occurs is how to create and publish each Research and community service activity by the P3M Polnam Center. With the aim of producing real-time information that can be accessed via the web. The framework used for this research is to communicate, analyze, design, construction, testing. So that later it will produce a Web for Polnam research and community service units.